Path analysis of arm muscle strength, leg power, and concentration on underhand passing performance in youth volleyball players - Wahid Adi Kusuma; Umar; M. Arnando; Alnedral; Ardo okilanda (CV. FOUNDAE, 2026)
Background: Volleyball is one of the most popular sports and requires effective underhand passing skills to maintain ball control during gameplay. Underhand passing performance is influenced not only by physical factors such as arm muscle strength and leg power but also by psychological factors, particularly concentration. However, the passing ability of junior volleyball players remains relatively low. Aims: This study aimed to analyze the effects of arm muscle strength, leg power, and concentration on underhand passing performance in youth volleyball players. Method: This study employed a quantitative associative design using a path analysis approach. The participants consisted of 30 male volleyball players aged under 15 years selected through total sampling. Arm muscle strength was measured using a pull-up test, leg power using a vertical jump test, concentration using the Concentration Grid Test, and underhand passing performance using a standardized volleyball passing test. Results: The findings showed that arm muscle strength contributed 16% to underhand passing performance, while leg power contributed 5.5%. Concentration also demonstrated a significant contribution to passing ability. Simultaneously, all variables showed a strong influence on underhand passing performance. Conclusion: Physical and psychological factors significantly affect volleyball underhand passing performance. Future studies are recommended to involve broader samples and different competitive levels.